Joint power differences in speed running between american style football position groups - Mokha, M.; Andal, A. A.; Haberer, J.; Hernandez, I. E.; Forte, H. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
We tested lower limb joint power during a treadmill run of 54 American style football players preparing for league try-outs where 40-yard (36.6 m) dash performance is critical. Players represented 3 position groups: Big (e.g., linemen), Big skill (e.g., tight ends), and Skill (e.g., receivers) groups, reflecting their varying play demands, from blocking/tackling to sprinting/cutting. MANOVA showed significant group differences in joint power, F(24,80) = 2.917, p < .001; Wilk`s lambda = .285, partial n² = .467. ANOVA and post-hocs revealed Skill players generated more total limb power than Big (p < .001) and absorbed more ankle power than Big (p < .001), but not Big skill (p > .017). Big absorbed more right hip power than Skill and Big skill (p < .05). Skill vs. Big showed the greatest contrasts, highlighting the need for ankle-specific conditioning exercises in preparation for the 36.6 m dash test.